CompTIA Cloud+ CVO-001 LiveLessons (sneak peek video training) - Dulaney, Emmett A.; Safari eBooks ([S.l.] : Pearson, 2014)
"CompTIA Cloud+ LiveLessonsis a unique video product that provides a solid understanding of cloud-based technologies and infrastructure. It looks at server, network, storage, and virtualization technologies and the aspects of IT security needed to implement industry best practices and pass the CompTIA Cloud+ certification exam. The product takes the student from an introduction to the fundamental concepts to a reasonably sophisticated understanding of the topics."--Resource description page.
Title from resource description page (viewed Mar. 28, 2014).
Presenter, Emmett Dulaney.
Keywords: Cloud computing; Electronic data processing; Electronic books